A novel green chemical mechanical polishing for potassium dihydrogen phosphate using corn oil slurry. (December 2022) - Cui, X.; Zhang, Z.; Shi, C.; Meng, F.; Xu, G.; Xie, W.; Liu, Z.; Wang, J.; Wen, W.
Abstract: Potassium dihydrogen phosphate (KH2 PO4, KDP) offers a promising potential for high-power laser and nuclear fusion systems. However, it is a great challenge to controllably process KDP crystal that is one of the most difficult-to-process materials due to its soft-brittle, deliquescence, and temperature sensitivity. In this work, novel green chemical mechanical polishing slurry was developed by utilizing corn oil, CeO2, Na2 CO3 solution, and polysorbate. After CMP, the surface roughness Sa of KDP is achieved to 0.648 nm with a large scanning area of 10, 000 μm 2 . To the best of our knowledge, this is the lowest surface roughness of KDP reported so far for such a large measurement area. During CMP, the encased small amount of Na2 CO3 solution in corn oil can be released under mechanical stress, which causes the bulges of KDP surface to form deliquescent soft layer and occur a bit of dissociation. Meanwhile, the reaction of CO3 2− and dissociated H2 PO4 − can produce CO2 gas, playing the role in protecting the concave area on the surface from being dissolved. These findings provide a promising avenue for the development of high-performance surfaces with the nature of soft-brittle and deliquescence.